DESIGN OF ENERGY EFFICIENT MAGNITUDE COMPARATOR ARCHITECTURE USING 3T XNOR GATE - K. VIRIJA (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
DESIGN OF ENERGY EFFICIENT MAGNITUDE COMPARATOR ARCHITECTURE USING 3T XNOR GATE